On the genus Schizaea in Peru - León, Blanca (2005)
The genus Schizaea includes conspicuous species in the Peruvian Amazon flora. Many species are soil specialists in oligotrophic conditions and have been reported from several localities in Peru. Increasing plant exploration in Peru in poorly known areas provide additions and novelties that require an update to the treatment of this genus for Peru